Locating Richard II in contemporary Athens. Issue 1 (July 2019) - Mitsi, Efterpi
In Act 2 Scene 2 of Richard II, Bushy advises the Queen against 'looking awry' upon the King's departure, comparing her gaze first to a perspective glass and then to a perspective picture that appears distorted unless viewed at an angle. I rely on this metaphor of anamorphosis to examine two recent productions of Richard II in Athens, both of which 'distort' the text and situate it in a bleak context. Viewed from the angle of the current political discontent, the 2014 and 2016 adaptations, directed by Elli Papakonstantinou and Efi Birba respectively, assume distinct meaning for the Athenian audience.